1998
DOI: 10.1111/j.1432-2277.1998.tb00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Intramucosal pH and intestinal mucosal damage in ischemia-reperfusion injury

Abstract: Small bowel transplantation (SBT) has become an increasingly promising treatment for short bowel syndrome. The evaluation of graft viability after SBT, however, has not been established, except by mucosal biopsy. We monitored intestinal mucosal acidity in order to detect small intestinal ischemia-reperfusion injury. Mongrel dogs were used in this study. After laparotomy, the small bowel was isolated with a vascular pedicle. A tonometer to measure intramucosal p H (pHi) was then positioned in the terminal ileum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…50, No. 1 (January 2005) between histological findings and the change in pH i and that monitoring intestinal mucosal acidity was a reliable way of determining graft viability after I/R (15). Furthermore, the mesenteric blood flow rate of the small bowel is known to decrease progressively after reperfusion of the autograft and the subsequent increase in the mesenteric vascular resistance (21).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…50, No. 1 (January 2005) between histological findings and the change in pH i and that monitoring intestinal mucosal acidity was a reliable way of determining graft viability after I/R (15). Furthermore, the mesenteric blood flow rate of the small bowel is known to decrease progressively after reperfusion of the autograft and the subsequent increase in the mesenteric vascular resistance (21).…”
Section: Discussionmentioning
confidence: 97%
“…Intramucosal pH (pH i ) was measured prior to ischemia, during ischemia, and at 1, 3, 6, and 12 hr after reperfusion. This method has been described previously (15). In brief, a tonometer (Trip; Tonometrics, Helsinki, Finland) was inserted into the small bowel lumen through a small incision in the bowel wall and secured with a purse-string suture.…”
Section: Methodsmentioning
confidence: 99%
“…Several experimental and clinical studies have extensively examined the hemodynamic and metabolic effects of superior mesenteric artery occlusion [4][5][6][7]. On the other hand, the cardiocirculatory derangement and the tissue damage induced by intestinal outflow obstruction have not been investigated systematically, despite their clear clinical importance. For these reasons, we have decided to assess the initial impact of venous mesenteric occlusion on intestinal mucosal and serosal blood flow distribution, and to correlate these findings with other systemic and regional perfusion markers.…”
Section: Introductionmentioning
confidence: 99%
“…Pre before ischemia, JBIR just before intestinal reperfusion, re-1 h after 1 h of reperfusion, re-3 h after 3 h of reperfusion, re-6 h after 6 h of reperfusion, re-12 h after 12 h of reperfusion perfusion [18]. We previously reported that there was a significant correlation between histological findings and the change in pHi and that monitoring intestinal mucosal acidity was a reliable way of determining graft viability after intestinal IR [13]. In addition, histopathological grading of the small intestine has been used to determine intestinal IR injury as well as the SMA blood flow rates in animal model studies of intestinal IR [4].…”
Section: Discussionmentioning
confidence: 98%
“…This method has been described previously [13]. In brief, a tonometer (Trip; Tonometrics, Helsinki, Finland) was inserted into the small intestinal lumen through the stoma.…”
Section: The Small Intestinal Tissue Blood Flow Measurementsmentioning
confidence: 99%